THE EFFECT OFCu-DOPING ON CRYSTAL STRUCTURE AND MAGNETORESISTANCE IN La0.73 Ca0.27 Mn1-y CuyO3 WITH 0 < y < 0.19 - Y E Gunanto; B Kurniawan; A Purwanto; Wisnu Ari Adi; S Poertadji (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2013)
THE EFFECT OFCu-DOPINGON CRYSTAL STRUCTURE AND MAGNETORESISTANCE IN La0.73 Ca0.27 Mn1-y CuyO3 WITH 0 < y < 0.19. We studied the crystal structure at room temperature and low temperature, as well as themagneto resistance as a functionmagnetic field at room temperature in the compound La0.73 Ca0.27 Mn1-y CuyO3 with 0 < y < 0.19. To analyze the crystal structure we used X-Ray Diffractometer (XRD) at room temperature and the neutron-powder-diffraction at room temperature and low temperatures. The neutron powder diffraction experiments were under taken with the High Resolution Powder Diffractometer (HRPD) (λ=1.8223 Å) at the Neutron Scattering Center of BATAN using the fullprof program. To analyze the magnetoresistance, we used a four point probe aparatus in the range ofmagnetic fields 0-7600 Oersted. we have found that no change in crystal structure despite of increasing value of y. All samples have structure orthorhombic with space group P nma, but the volume of lattice in low temperature is smaller than room temperature. At room temperature, increasing the value y impact declining value of magneto resistance.